PENERAPAN PROGRAM LINIER MENGGUNAKAN METODE DUAL SIMPLEKS DAN METODE QUICK SIMPLEKS UNTUK MEMINIMUMKAN BIAYA (STUDI KASUS: KELOMPOK WANITA TANI (KWT) SENTOSA SANTUL) - Elfira - Safitri; Sri Basriati; Elvina Andiani (Journal of Fundamental Mathematics and Applications (JFMA), 2021)
The Sentosa  Santul Women Farmers Group (KWT) is a group of women farmers in Dusun Santul, Kampar Utara District an is engaged in the field of food crops is chili. The Sentosa Santul Women Farmers group (KWT) uses 4 types of fertilizers for chili plant fertilization, namely hydro complex fertilizer, phonska, NPK Zamrud and goat manure.The KWT wants the minimum fertilizer cost but the nutrients in the plants are met. The method used in this research is the dual simplex method and the quick simplex method. The purpose of this study is to determine the minimum costs that must be incurred by the Womens Farmer Group (KWT) for fertilization using the dual simplex method and the quick simplex method to obtain an optimum and feasible solution. For the dual simplex method, the optimum and feasible solution were obtained using the Gauss Jordanelimination. While the quick simplex method, the solution is illustrated using a matrix to reduce the number of iterations needed to achieve the optimal solution. Based on the research result, it is found that the quick simplex method is more efficient than the dual simplex method. This can be seen from the number of iterations carried out. Dual simplex method iteration there are two iterations and quick simplex one iteration. The dual simplex method and the quick simplex method produce the same value.